Immunophenotyping Reveals the Diversity of Human Dental Pulp Mesenchymal Stromal Cells In vivo and Their Evolution upon In vitro Amplification - Ducret, Maxime; Fabre, Hugo; Degoul, Olivier; Atzeni, Gianluigi; McGuckin, Colin; Forraz, Nico; Mallein-Gerin, Frédéric; Perrier-Groult, Emeline; Alliot-Licht, Brigitte; Farges, Jean-Christophe (Frontiers in Physiology, 2016)
Mesenchymal stromal/stem cells (MSCs) from human dental pulp (DP) can be expanded in vitro for cell-based and regenerative dentistry therapeutic purposes. However, their heterogeneity may be a hurdle to the achievement of reproducible and predictable therapeutic outcomes. To get a better knowledge about this heterogeneity, we designed a flow cytometric strategy to analyze the phenotype of DP cells in vivo and upon in vitro expansion with stem cell markers. We focused on the CD31− cell population to exclude endothelial and leukocytic cells. Results showed that the in vivo CD31− DP cell population contained 1.4% of CD56+, 1.5% of CD146+, 2.4% of CD271+ and 6.3% of MSCA-1+ cells but very few Stro-1+ cells (≤ 1%). CD56+, CD146+, CD271+, and MSCA-1+ cell subpopulations expressed various levels of these markers. CD146+MSCA-1+, CD271+MSCA-1+, and CD146+CD271+ cells were the most abundant DP-MSC populations. Analysis of DP-MSCs expanded in vitro with a medicinal manufacturing approach showed that CD146 was expressed by about 50% of CD56+, CD271+, MSCA-1+, and Stro-1+ cells, and MSCA-1 by 15–30% of CD56+, CD146+, CD271+, and Stro-1+ cells. These ratios remained stable with passages. CD271 and Stro-1 were expressed by <1% of the expanded cell populations. Interestingly, the percentage of CD56+ cells strongly increased from P1 (25%) to P4 (80%) both in all sub-populations studied. CD146+CD56+, MSCA-1+CD56+, and CD146+MSCA-1+ cells were the most abundant DP-MSCs at the end of P4. These results established that DP-MSCs constitute a heterogeneous mixture of cells in pulp tissue in vivo and in culture, and that their phenotype is modified upon in vitro expansion. Further studies are needed to determine whether co-expression of specific MSC markers confers DP cells specific properties that could be used for the regeneration of human tissues, including the dental pulp, with standardized cell-based medicinal products.